Estudo de caso de um salão de beleza: o adoecimento físico de sócias cabeleireiras - Gabriela Cristina Cardoso Silva (2010)
The aim of this paper is to study the work activity developed by hairdressers, as the postures adopted and maintained while they are working and there possible relationship with repetitive strain injuries. The informal registrations of physical deterioration are based on the signs and symptoms that were reported by work ergonomic analysis which were studied deeply into the matter in this paper, searching for reference books that contain information about this subject. Countless methods were used for elaboration of this thesis, as systematic observations of the activity and studies of body techniques, basing on the report of work ergonomic analysis, aiming to understand the dynamics and the daily activities of the hairdressers. After studying and systematically observing the hairdressers' duties, mainly the hair brushing activity, in accordance with the concept of RSI/DORT, it was possible to verify the possibility of developing occupational disease. It was demonstrated that the body postures adopted during their activities, particularly the time spent maintaining these postures and the inadequacy of their work instruments, might deteriorate their physical health.